Causal analysis of dietary preferences and the risk of endometriosis using large-scale population data - Xin Cheng; Dan Ma; Xiuhong Wang; Meiling Li; Jinpeng Jiang (Scientific Reports)
Abstract Dietary factors have recently been recognized as potentially influential in the pathogenesis of endometriosis (EM), yet studies on the causal relationship between dietary preferences and EM are limited. The present study aimed to explore the causal relationships between 187 dietary preferences and EM using Mendelian randomization (MR) methods. This study utilised genome-wide association study data from over 500,000 European participants for dietary preferences and 64,658 EM patients from Finland. Dietary preferences with potential causal relationships to EM were identified using two-sample MR methods. P-values from the inverse variance weighted (IVW) analysis were corrected using the false discovery rate (FDR) method to ensure accuracy. Additionally, heterogeneity analysis, pleiotropy assessment, leave-one-out analysis, and reverse MR analysis were conducted to further validate and solidify the findings of the study. After FDR correction, IVW analysis revealed that asparagus preference was significantly protective against EM, including in American Society for Reproductive Medicine (ASRM) stages 1–2 and 3–4. Conversely, preferences for different types of coffee and orange juice were associated with an increased likelihood of EM across these stages. Subgroup analysis indicated that asparagus preference had a protective effect against deep EM, ovarian EM, pelvic peritoneal EM, and rectovaginal septum and vaginal EM. In contrast, coffee preference increased the risk of pelvic peritoneal EM, fallopian tube EM, and unspecified EM, whereas orange juice preference increased the risk of deep EM, rectovaginal septum and vaginal EM, pelvic peritoneal EM, and unspecified EM. Reverse MR analysis did not identify causal relationships between EM and the specific dietary preferences that were analysed in this study. These findings suggest that asparagus preference significantly reduces the risk of developing EM, whereas preferences for orange juice and different types of coffee may increase the risk, offering new insights into EM management through dietary modifications.